SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MEDIA PEMBELAJARAN DARING DI SD NEGERI 048/IX SARANG BURUNG MENGGUNAKAN METODE HYBRID AHP-TOPSIS - Kahar, Novhirtamely; Wahyuning Astuti, Reny; Mubaroq, Fazri (LP2M Universitas Nurdin Hamzah, 2024)
This study focuses on selecting online learning media at SD Negeri 048/IX Sarang Burung. Various available media options often make it difficult for educators to choose the one that best suits the needs and conditions of the student environment. This study uses the Hybrid AHP-TOPSIS approach to design a decision support system. The AHP method is used to establish a hierarchy of relevant criteria and their relative weights. Meanwhile, the TOPSIS method is used to rank alternative learning media based on their proximity to the ideal positive and negative solutions. This system is built using web-based software that allows users to input data and view analysis results directly. The system testing results show that the Hybrid AHP-TOPSIS method can produce selected learning media alternatives that meet user needs, specifically Zoom with a score of 0.8667. Thus, the system testing results indicate that the Hybrid AHP-TOPSIS method can produce selected alternatives according to user needs, and the implementation of this system can improve education quality because the proper selection of learning media can enhance students' motivation and learning outcomes. Additionally, this system is expected to be a solution to the problems in determining appropriate learning media for educators.